Analisis Peran Ojk dalam Penerapan Manajemen Risiko pada Lembaga Keuangan Non-Bank di Indonesia - Hanisa Mafinanik; Abd. Karman (Yayasan Literasi Sains Indonesia, 2025)
This study analyzes the role of the Financial Services Authority (Otoritas Jasa Keuangan/OJK) in implementing risk management within non-bank financial institutions (NBFIs) in Indonesia. Established under Law No. 21 of 2011, OJK operates as an independent regulatory body responsible for supervising, regulating, and enforcing compliance in the financial services sector. Using a qualitative descriptive approach, this research examines regulatory frameworks, policy documents, and implementation practices of OJK Regulation No. 44/POJK.05/2020, which mandates NBFIs to apply comprehensive risk management covering strategic, operational, credit, liquidity, market, compliance, and reputational risks. Implementation requires active oversight by the board of directors and commissioners, the establishment of adequate policies, and the strengthening of internal control systems. The analysis reveals that effective risk management significantly enhances corporate governance and contributes to national financial stability. Moreover, compliance with OJK regulations serves as a critical instrument for institutional risk mitigation. Conceptually, this study enriches the understanding of supervisory effectiveness in non-bank financial sectors and provides a foundation for developing more adaptive regulatory policies in response to the evolving dynamics of financial risk in Indonesia.